POE를 적용한 논술형 탐구학습 프로그램 활용 수업이 고등학생들의 학업 성취도와 과학 관련 태도에 미치는 효과 - 김동렬; Dong Ryeul Kim (과학교육연구지, 2009)
본 연구는 고등학교 생물 수업에서 POE를 적용한 논술형 탐구학습 프로그램의 개발 및 수업에의 적용으로 학생들의 학업 성취도와 과학 관련 태도에 미치는 효과를 알아보고자 하였다. 연구 대상으로 부산시소재의 남자 인문계고등학교 2학년 4개 반을 선정하였다. 수업은 생물Ⅰ `순환` 단원으로 4주에 걸쳐 6차시로 이루어졌으며, 실험집단은 POE를 적용한 논술형 탐구학습 프로그램에 의거한 수업을 진행 하였으며, 통제집단은 실험집단과 동일한 학습 목표와 주요학습 내용을 기준으로 생물Ⅰ 교과서에 제시되어 있는 학습내용과 탐구활동을 토대로 실시하였다. 현장적용결과, 첫째, POE를 적용한 논술형 탐구학습 프로그램은 이미 알고 있는 지식과 실험을 통해 새롭게 알게 된 지식을 적절하게 연결하는 활동과 학생들의 고차원적인 사고유발을 위한 교사의 다양한 질문을 통해 문제해결력 향상뿐만 아니라 논리적인 사고능력에 도움을 주어 학업 성취도에 긍정적인 효과를 미친 것으로 나타났다. 둘째, POE를 적용한 논술형 탐구학습 프로그램은 실험에 대한 사전 예측활동으로 실험에 대한 관심을 유발하게 하고 직접 관찰한 것과 예측한 것 사이의 모순을 해결해 가는 과정을 통해 학습과정에 적극적인 참여의 유도로 과학 관련 태도에 긍정적인 효과가 나타난 것으로 판단된다. The research is aimed at investigating the development and application of high school biology classes utilizing discourse-typed inquiry learning program fitted with POE, and the corresponding effect on student`s academic achievement and attitude toward science. 4 classes of 11th graders in a general high school located in Busan were selected as subjects. Biology I, `Circulation` unit was lectured for 4 weeks (6 classes), and the experimental group underwent classes utilizing discourse-typed inquiry learning program fitted with POE. The control group was taught identical major learning contents, but based on the learning objectives and research activities provided by Biology I textbook. As a result of application, first, the discourse-typed inquiry learning program fitted with POE exhibited positive consequences of linking previously acquired knowledge and the new learning attained through experiments, as well as not only improving the students` problem solving capacity through diverging questions from the teachers to drive the students` higher-level contemplation, but also enhancing student academic achievement by assisting their logical thinking. Second, POE-fitted discourse-typed inquiry learning program rendered presupposing session of the experiment that resulted in drawing learners` attention in advance, and incited active participation in the learning process through solving the contradiction between what was actually observed and what was expected, which eventually proved to lay out positive impact on students` attitude toward science.